Reflections on Ideologies Underpinning ELT Curriculum and Nature of Global Course Books Used in Saudi Arabia - Anwar, Muhammad Mansoor; Alhoussawi, Hussain (International Journal of Linguistics, 2023)
The influence of neoliberal ideology in the educational literature has widely been discussed recently. Yet relatively little critical attention has been paid to the ways these hegemonic agendas have shaped and influenced the development of ELT curriculum and published teaching materials. This theoretical paper reviews literature on how neoliberal ideology influences ELT curriculum, namely published teaching materials. Also, it argues that ELT curriculum contents are essentially political and ideologically constructed to fulfil the politico-economic interests of ELT international publishers, located in the centre (e.g., UK and US). These neoliberal ideological constructions are preparing our students to become neoliberal citizens, consumers, or customers of English language learning, who can become apt members of callous marketization. This theoretical paper recommends that TESOL professionals need to play their role by demystifying and resisting these ideologies by redesigning the ELT curricula, such as course books. In addition, scripted curriculum and one-size-fits-all policy reflected in global course books contents do not fulfil the needs of diverse learners in various EFL/ESL contexts. Therefore, TESOL professionals, in particular teachers and academics need to be aware of current and potential educational policies and advocacies driven by western neoliberal educational ideologies. In practice, ESL/EFL teachers, academics and curriculum developers are required to consider their contextual local realities, such as students' English language learning constraints and teaching perspectives from teachers stand points in designing the EFL/ ESL curriculum contents.